Socioeconomic and contextual factors associated with low academic performance of Peruvian students in PISA 2015 - Muelle, Luis Edgardo (2019)
This study applies a logistic multilevel analysis to the test results of Peruvian students in science, mathematics, and reading in the PISA 2015 round. It focuses on measuring the impact of student socioeconomic and contextual factors on low academic performance. The socioeconomic status of the students and the socioeconomic composition of the school appear to be the main factors that affect the poor performance. Other contextual factors, such as repetition, mother tongue, school size, grade, non-truancy and gender, are associated with low achievement. It is also worth highlighting the presence of non-contextual emotional factors that affect academic risk such as sense of belonging to a school, achievement motivation, and test anxiety.